2020
DOI: 10.1007/s10608-020-10126-z
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Mentalizing, Empathy and Symptoms in People with Eating Disorders: A Network Analysis Integrating Experimentally Induced and Self-report Measures

Abstract: Background. The role of mentalizing and empathy in the socio-emotional processing deficits of Eating Disorder (ED) patients has been under investigated. We aimed to assess these psychological processes and their interplay with ED symptoms by means of the network analysis approach.Methods. Seventy-seven women with EDs completed self-report questionnaires assessing ED, anxious and depressive symptoms, and underwent two computerized tasks; the Movie for the Assessment of Social Cognition (MASC), assessing emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 53 publications
2
28
1
Order By: Relevance
“…More studies are also needed to explore the connections between psychopathology and the external field through network analysis, an area of investigation that has been already emphasised in EDs (Levinson et al., 2018; Smith et al., 2018). The findings of our review demonstrate that, so far, this area of investigation includes only two studies (Monteleone et al., 2019, 2020b) assessing the connection of ED psychopathology with childhood traumatic experiences or socio‐cognitive deficits and few studies investigating in terms of centrality the connection with personality dimensions (Solmi et al., 2018; Vervaet et al., 2020) and identity (Cascino et al., 2019).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…More studies are also needed to explore the connections between psychopathology and the external field through network analysis, an area of investigation that has been already emphasised in EDs (Levinson et al., 2018; Smith et al., 2018). The findings of our review demonstrate that, so far, this area of investigation includes only two studies (Monteleone et al., 2019, 2020b) assessing the connection of ED psychopathology with childhood traumatic experiences or socio‐cognitive deficits and few studies investigating in terms of centrality the connection with personality dimensions (Solmi et al., 2018; Vervaet et al., 2020) and identity (Cascino et al., 2019).…”
Section: Discussionmentioning
confidence: 83%
“…In accordance with this study, early maladaptive schema (over‐vigilance and inhibition of emotions and impaired autonomy and performance) were external field nodes resulting highly central in samples with mixed EDs (Vervaet et al., 2020), although their possible bridge role was not assessed. Another study (Monteleone, Corsi, et al., 2020) explored the connections of ED‐specific and affective symptoms with mentalizing and empathy, assessed through experimental tasks, and displayed emotional mental state inference and restraint as the bridge nodes between psychopathology and socio‐cognitive processes. This was the only study including data from multiple levels of assessment in an ED network.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, imitation should be considered a distinct process from mentalizing and empathy, although they likely interact in determining everyday social competence (Bird & Viding, 2014;Happé & Frith, 2014). Support for the interaction between socio-cognitive processes and psychopathology has been provided by a previous network analysis exploring the associations between mentalizing, empathy, affective symptoms and eating disorder psychopathology in the eating disorder sample described in the current study (Monteleone et al, 2020). Findings from that study indicated that mentalizing and empathic processes interact with each other and with eating disorder and affective symptoms, and that this interplay contributes to the maintenance of eating disorder psychopathology.…”
Section: Discussionmentioning
confidence: 60%
“…Development of the NA approach over the past decade has provided a theoretical framework that was adopted to identify the central symptoms of different psychiatric disorders, such as bipolar disorder [15], depression [16], obsessive compulsive disorder [17] and schizophrenia [18]. More recently, researchers in the field of eating disorders have applied NA to examine the symptoms of anorexia nervosa [19][20][21][22] and bulimia nervosa [23][24][25].…”
Section: Introductionmentioning
confidence: 99%